Influence of Dietary Habits on Atherosclerosis - Leena Joseph P (Department of Home Science, College of Agriculture, 1990)
A study on the influence of dietary habits on atherosclerosis was conducted among patients attending the Cardiac clinic at Medical College. Trivandrum. An assessment of the socio economic and food consumption pattern of the families of atherosclerotic patients. personal characteristics as well as dietary pattern of the patients and the effect of diet counselling which was imparted to selected case studies was also made. The results of the socio economic and dietary survey conducted in 100 families of the atherosclerotic patients, attending the Cardiac clinic at Trivandrum Medical College, revealed that, most of the patients belonging to the low socio economic group, resided in the rural areas and were habitual non vegetarians (95 per cent). Around 63 per cent of the families spent upto 60 per cent of their monthly income on food, purchasing staple food articles like cereals and roots and tubers weekly, perishable foods like milk, fish, leafy vegetables and other vegetables daily, and other foods like oilseeds, cooking oils, sugar and spices and condiments monthly. Pulses, fruits, meat and egg were purchased only occasionally by majority of the families. All the families used rice daily but majority of them were not in the habit of using